PENERAPAN MODUL BERBASIS DISCOVERY LEARNING UNTUK MENGATASI MISKONSEPSI SISWA PADA MATERI SEL DI MAN DARUSSALAM - Putri Wulandari; Khairil Khairil; Safrida Safrida (Biotik, 2017)
This study was designed to know the implementation of discovery-based learning modules to resolve misconceptions. The data were collected on June, 2016. An experimental method with pretest posttest control group design was conducted at MAN Darussalam. The samples were students of class XI IA 1 as the control class and students of class XI IA 3 as the experimental class. The instrument used was a test to measure students’ misconceptions. To analyze the data, the researcher used percentage formula. The results showed that the concept of chemical components of cells decreased by 25%, the concept of the structure and function of cells decreased by 15%, the concept of animal and plant cell organelles decreased by 6% misconceptions and the concept of transport through the membrane increased by 2%. It was concluded that the discovery-based learning modules could solve students’ misconceptions in the cell concepts at MAN Darussalam.